Sintesis dan Karakterisasi Kompleks Ni(II)-EDTA dan Ni(II)-Sulfanilamid - Triyani, Nur Farida (Chem Info Journal, 2013)
A study entitled Synthesis and Characterization of Complex Ni (II)-EDTA and Ni (II)-sulfanilamide. This study aimed to obtain complex compounds are formed [Ni (EDTA)] and [Ni (slf)3(H2O)3] and know the complex characterization of Ni (II)-EDTA and Ni (II)-sulfanilamide with analysis using UV -Vis, FTIR and AAS. Synthesis of complexes Ni (II)-EDTA done with 2:2 ratio, whereas Ni(II)-sulfanilamide done with 2:6 ratio. The final results were analyzed using UV-Vis wavelength for the determination of the maximum. FTIR analysis to determine functional group compounds and complex interactions between the metal and the ligand. AAS analysis done to determine how many metal atoms are bound to the ligand. FTIR results showed the acquired group O and group N on EDTA center coordinated to Ni2+ ions form complexes Ni(II)-EDTA, while the amine nitrogen groups coordinated to the central Ni2+ ions form complexes Ni(II)-Sulfanilamide. UV-VIS spectra result in the absorption peak for the complex Ni (II)-EDTA at 594 nm and 772 nm at 10 Dq at 201.207 and 154.815 kJmol-1 kJmol-1, while the maximum absorption of Ni(II)-sulfanilamide at 407 nm and 742 nm at 10 Dq at 298.047 and 161.074 kJmol-1 kJmol-1. Ni (II)-EDTA = 3,544 log Kstab more stable than Ni (II)-sulfanilamide log Kstab = 3,48.